Advances in Air Navigation Services - Magister, Tone (IntechOpen, 2012)
Provision of air navigation services entered a new era of performance scheme. The performance scheme provides binding targets on four key performance areas of safety, capacity, environment and cost-efficiency. It is imposed that targets are fully achieved, but it is not prescribed how, this being typical for the performance based and goal oriented regulation. Those key performance areas are interlaced by proportional and inversely proportional interdependencies. Namely, for example and simplified into one sentence; if one aims to increase sector capacity with existing human resources (constant staff costs) and not investing into the technology (constant support cost) to achieve improved cost-efficiency of service provision, the resulting overloaded system might unlock the Pandora box of latent safety issues. Since failure is not an option, we - the general, migrating and traveling public, airspace users, airport operators, air navigation services providers and the economy - will gain attaining the goals of performance scheme in the process. However, un-answered cardinal question is what is the winning strategy? This book provides do-not-forget-peculiarities insight into the elements of new business model of air navigation services provision as evolution of the latter became essential.